Pengaruh Kepercayaan Diri Seorang Public relation dalam Berkomunikasi - Chyntania Chantika Triana; Anita Yulianti; Lisna Azka Nuraeni; Adillah Siti Sayyidah (Cebong Journal, 2022)
This study aims to analyze and understand about the influence of a public relation's confidence in communicating. Confidence as the initial part of public relations and public speaking activities in communication, is very interesting to research, considering that public relations will be awakened if they have confidence in communication. This study uses a library method in which activities related to the collection of library data derived from journals, books, and also trusted communication websites related to the influence of confidence of a public relationThe results showed that the influence of confidence of a public relation in communicating can be overcome by increasing confidence by having a strong and able to put yourself in all situations. The confidence of a public relations officer is very important because, from that confidence, we can know and easily carry out a communication, both for the public and for ourselve.